THE EIFELIAN VEGETATION AND RECONSTRUCTED LANDSCAPES OF CENTRAL KAZAKHSTAN - Yurina A.L.; Belyaev O.E. (My University, 2000)
The taxonomic composition and structure of Eifelian plant communities of central Kazakhstan and the orogeny-influenced distribution of taxa are discussed. Circular diagrams are plotted for individual floral taxa from sedimentary formations of strictly continental genesis and from those including marine sediments. The data obtained, as well as plant life forms and a relief differentiation, are taken into account in the reconstruction of Eifelian landscapes of the Devonian volcanic belt and some adjacent Hercynides areas. The and dissected relief of the volcanic belt was characterized by more abundant diverse vegetation than the deltaic marshes or flooded terraces in the Hercynides areas. In both cases, there was no continuous vegetation cover and the plants grew in isolated areas, which were either damp or located near water basins.
Keywords: Eifelian; Paleozoic::Devonian::Middle::Eifelian; Палеозой::Девонская::Средний::Эйфельский